What educational activities fit virtual worlds: towards a theoretical evaluation framework - Jaeger, Bjoern (IEEE Industrial Electronics Society, 2009)
Many universities and colleges are investing in teaching and learning developments in virtual worlds despite a lack of any clear guidelines or rules for when virtual worlds will provide benfits over established communication media. Among activities that have been successfully tried out so far are interpersonal role play and oral language education, while other practices like traditional lecturing and business transaction oriented role plays seem to be less suitable for successful implementation. Our objective in this paper is to develop an evaluative framework educational for educational activities in virtual worlds based on Media Richness and Task Closure Theories from Management Informatin Systems. We demonstrate the use of the framework for three educational activities conducted in the virtual world of Second Life.